Activated graphene nanosheets/spinule-like Ni(OH)2 composite as cathode materials for high performance supercapacitors. (1st December 2018) - Yang, Hui-Xian; Zhao, Dong-Lin; Lin, Huan; Tian, Xin-Min; Han, Xin-Yao; Duan, Ya-Jing; Zhao, Min
Abstract: Nickel hydroxide is widely utilized for the cathode material of asymmetric supercapacitors due to high electrochemical performance and low cost. However, considering its poor electrical conductivity as well as short cycle life, Ni(OH)2 is not capable of applying to high performance supercapacitors. An efficient solution is to fabricate the activated graphene nanosheets (AGNSs)/spinule-like Ni(OH)2 composite by controllable complex-precipitation method. The electrochemical measurement results demonstrate that AGNSs/spinule-like Ni(OH)2 composite as cathode material for supercapacitor has high specific capacitance of 2450 F g −1 at 1 A g −1 and excellence cycling capacity (1499 F g −1 after 5000 cycles at 10 A g −1 ). The asymmetric supercapacitor (ASC) displays a superior energy density of 55.6 Wh Kg −1 at power density of 1628 W kg −1, as well as rate capacity. These excellent electrochemical properties are attributed to the synergy effect of activated graphene and nickel hydroxide. Graphical abstract: AGNSs/spinule-like Ni(OH)2 composite was prepared by a simple controllable complex-precipitation method. The structure of AGNSs/spinule-like Ni(OH)2 composite helps the spinule-like Ni(OH)2 and AGNSs to achieve a strong affinity, which leads to strong synthetic effects between both materials. AGNSs/spinule-like Ni(OH)2 composite exhibit a high energy density (87.7 Wh Kg −1 at power density of 351 W kg −1 ) and excellent cycle life (1499 F g −1 after 5000 cycles at a current density of 10 A g −1 ). Highlights: AGNSs/spinule-like Ni(OH)2 composite was prepared by a simple method. The unique structure of AGNSs/spinule-like Ni(OH)2 composite can improve electrochemical performance. The high specific capacitance and excellence rate capacity of AGNSs/spinule-like Ni(OH)2 composite has been achieved. The superior energy density and power density have been obtained in ACS.